Effect of Supervisory Leadership on Discipline, Dedication and Its Implications on Teaching Competence of English Teachers in the Digital Era - Masrur, Masrur (Dinamika Ilmu: Jurnal Pendidikan, 2020)
For this study, the focus will be on evaluating the impact of supervisory leadership on the professionalism of Samarinda's English instructors in the cyber era. MTs principals and English instructors were the subjects of the investigation. A descriptive quantitative technique is adopted in this study. Observation, questionnaires, and documentation were used for data collection, and regression is used for data analysis. There were 110 participants in this study's population, which included principals and English teachers from public and private MTs in Samarinda. As a result of the need for observation and knowledge, the study was conducted at public and private MTs throughout Samarinda, with the purpose of examining the Effect of Supervisory Leadership on Discipline and Dedication and its Implications on Improving the Teaching Competence of English Teachers in Public and Private MTs throughout Samarinda during the Digital Era. The findings demonstrate that supervisory leadership through discipline indicates an indirect and significant impact on the teaching competency of English teachers in both public and private MTs in Samarinda. Furthermore, these findings demonstrate that the supervisory leadership, as evidenced by his or her dedication, has a substantial impact on the teaching competency of English teachers in both public and private MTs across Samarinda.